2021
DOI: 10.3727/152599519x15506259856615
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership, Empowerment, and Positive Outcomes: Hearing the Voices of the Events Industry

Abstract: The purpose of this study is to investigate the direct and indirect relationships between authentic leadership and job satisfaction; and those between authentic leadership and organizational commitment, using empowerment as a mediator in the events industry. Quantitative data were obtained from 304 participants from sport, cultural, and personal events in the Middle East. Three hundred and four surveys were completed. The results show that empowerment mediates the relationships between authentic leadership and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(81 reference statements)
1
4
0
Order By: Relevance
“…This finding suggests that employees tend to be more intensely devoted to organizational tasks when leaders demonstrate leadership authenticity (AL). The results of earlier studies by Tijani and Okunbanjo (2020), Megheirkouni (2021), Alomari, Alharafsheh, and Nofal (2019), Duarte, Ribeiro, Semedo, and Gomes (2021), as well as Roncesvalles and Gaerlan (2021) are in agreement with this finding. This study also put out the hypothesis that among workers, AL greatly predicted OT (H2).…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…This finding suggests that employees tend to be more intensely devoted to organizational tasks when leaders demonstrate leadership authenticity (AL). The results of earlier studies by Tijani and Okunbanjo (2020), Megheirkouni (2021), Alomari, Alharafsheh, and Nofal (2019), Duarte, Ribeiro, Semedo, and Gomes (2021), as well as Roncesvalles and Gaerlan (2021) are in agreement with this finding. This study also put out the hypothesis that among workers, AL greatly predicted OT (H2).…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…Using data collected from 281 employed businesspeople in Australia, Lux, Grover, and Teo (2019) examined how AL related to affective commitment and found that AL strongly predicted affective commitment. Also, Megheirkouni (2021) investigated the relationship between AL and OC. This study's data came from 304 workers in Syria, Lebanon, and the United Arab Emirates, and this researcher found that AL predicted OC.…”
Section: Authentic Leadership and Organizational Commitmentmentioning
confidence: 99%
“…For us, a particularly pressing concern is the lack of research into the role of leadership within the process of event management. Our review of the literature revealed only a handful of empirical research papers that focused on leadership, including some of our own work, e.g., Abson (2017); Abson & Schofield (2022); Megheirkouni (2018Megheirkouni ( , 2021Megheirkouni ( , 2022; Wahab, et al(2014). This lack of research into event leadership is understandable given the dynamic and complex environment in which event managers work (Imam & Zaheer, 2021).…”
Section: Event Leadership Matters: Why a Shared Approach Might Be The...mentioning
confidence: 97%
“…See, for example, research into ethical, servant and shared leadership in tourism and hospitality (e.g., Dhar, 2016;Elche et al, 2020;Fu et al, 2020). Event scholars, however, are still too often focused on descriptive characteristics and skills needed to manage events; this is true even of the empirical studies which focus on leadership styles (Megheirkouni, 2018(Megheirkouni, , 2021(Megheirkouni, , 2022Wahab et al, 2014) or the competencies and skills needed to lead events (Abson, 2017;Giudici & Filimonau, 2019;Werner et al, 2022;Padron & Stone, 2019). They also often fail to engage with the particular challenges that surround leadership in events.…”
Section: Event Leadership Matters: Why a Shared Approach Might Be The...mentioning
confidence: 99%
“…The results of sport event research indicate that particular leadership behaviors or styles may refer to 'responsibility' when they help achieve positive outcomes. For example, transformational leadership, servant leadership, authentic leadership were perceived as effective in the sports event sector (Megheirkouni, 2017a;Megheirkouni, 2019a;Megheirkouni, 2021;Megheirkouni et al, 2018). Studies have also revealed that servant leaders are perceived as responsible leaders when they put others first (Megheirkouni, 2018b;Parris & Peachey, 2013;Rieke et al, 2008;Wells & Welty Peachey, 2016), while in other published research, it has been suggested that effective leaders are those who seek to build high-quality LMX relationships (Bang, 2011;Cranmer & Myers, 2015, Hoye, 2004Megheirkouni, 2017c;Megheirkouni, 2020).…”
Section: Introductionmentioning
confidence: 99%